LATITUDINAL CHANGE OF NORMAL PARAFFIN COMPOSITION IN THE NORTHWEST PACIFIC SEDIMENTS - Yamamoto K.; Kurata Y.; Takayanagi Y.; Nishimura A.; Mimura K. (My University, 2003)
We analyzed normal saturated paraffins (n-paraffins) in 70 surface sediments in the northwest Pacific to examine the spatial distribution of organic materials. All sediments show bimodal n-paraffin abundance patterns against carbon number with maxima at C16 and C31, indicating that n-paraffins in marine sediments are a mixture of long-chain n-paraffins from land-based higher plant waxes and short ones from marine organisms. We observed in this study a significant change of carbon preference index (CPI) from 2.5 in low latitudes to 4.5 in mid-high latitudes around 19-25°N. The following influences are discussed as the cause of CPI offset between low and mid-high latitudes: (1) meteorological conditions, (2) n-paraffin composition of higher land plants, (3) contribution of petroleum components, and (4) mixing ratio of higher land plants and marine organisms. However, none of them can be the possible cause of the CPI offset. Because n-paraffin content and composition vary significantly according to the species of a bacterium, difference of the species of bacterial communities between low and mid-high latitudes may be a possible reason for the CPI offset found in sediment from the northwest Pacific.
Keywords: PACIFIC OCEAN; MARINE SEDIMENTS; N-PARAFFIN; CARBON PREFERENCE INDEX